Ratio of sperm, oocytes and water for artificial fertilization of Brycon insignis (Characiformes: Characidae) - Seabra de Souza, Ana R. [UNESP]; Mori, Yuugo S. [UNESP]; Andrade, Suelen A. P. [UNESP]; Valandro, Janaína S. I. [UNESP]; Caneppele, Danilo; Sanches, Eduardo Antônio [UNESP] (Hindawi, 2022)
To promote the maximum fertilization rates (FRs) and normal embryonic development, the appropriate ratio of motile sperm to oocytes and adequate water volume should be applied in fish. Therefore, the aim of this study was to determine the proportion of “sperm: egg: water” for maximum use in artificial fertilization in Brycon insignis. A completely randomized experimental design in a factorial scheme (4 × 4) was applied that consisted of four inseminating doses (50,000, 350,000, 650,000 and 950,000 mobile sperm per oocyte), and they were activated with four different volumes of water (1, 5, 10 and 15 ml g−1 of oocytes), performed in triplicate. There was a significant effect on the FR (p < 0.05; R = 69.5%) and hatching rate (p < 0.05; R = 64.2%) with a linear increasing effect up to 152,172 and 130,870 mobile sperm oocytes−1 ml−1 of water respectively. Furthermore, to fertilization and hatch rates, the significative effects (p < 0.05) were verified on surface response model with lower rates when the large water volume and low sperm quantity were applied. On the other hand, low volumes of water, with low or high sperm doses, produced better results. In other words, large amounts of water can only be applied when associated with high amounts of sperm. For the percentage of normal larvae, there was significant difference (p < 0.05) on surface response model, with higher values to intermediary sperm doses and water volume. Thus, B. insignis reproduction can be optimized if the ratio of semen (0.68 ml): oocytes (100 g): water (100 ml) is applied to the procedure.
Keywords: dry fertilization; fish gametes rate; fish reproduction; fish sperm quality; neotropical fish; piabanha